Environmental and Personality Factors as Correlates of Psychological Adjustment of Adolescents with Hearing Impairment in Secondary Schools in Oyo State, Nigeria (2011)
Adolescents with hearing impairment are often viewed as individuals who are psychologically maladjusted as a result of poor environmental and personality factors. Consequently, their senses of belonging in the society have been reduced to the extent that their self image have been affected. Although, several studies on adolescents with hearing impairment have focus on their academic performance, but little attempt have been made to examine or study the environmental and personality factors. This study, therefore, examined the environmental and personality factors as correlates of psychological adjustment of adolescents with hearing impairment in secondary schools in Oyo state, Nigeria. The survey research design was adopted. The Purposive sampling technique was used to select 233 adolescents with hearing impairment from four integrated secondary schools in Ibadan, Oyo and Ogbomoso, Oyo State. Four research instruments were used for data collection: Adolescents Home and School Adjustment Questionnaire (r=0.86), personality types Questionnaire (r=0.84), Adjustment to Hearing Loss Questionnaire (r=0.83) and Psychological Adjustment Inventory (r=0.68). Three research questions were answered and six hypotheses were tested at the 0.05 level of significance. Data were analysed using descriptive statistics, Pearson Product Moment Correlation, Chi Square and Multiple Regression. Home environment (r=0.812, p< 0.05) and school environment (r=0.773, p< 0.05) were positively correlated with psychological adjustment of adolescents with hearing impairment. Home environment, school environment, age of onset and degree of hearing loss significantly predicted psychological adjustment of adolescents with hearing impairment (F(4,226) = 1014.54 p<0.05) and contributed 94.7% of the total variance to the dependent variable. However, age of onset and degree of hearing loss were not significantly correlated with psychological adjustment of adolescents with hearing impairment. Also, there were no significant associations among personality types, gender and psychological adjustment of adolescents with hearing impairment. The relative contributions of the independent variables to the psychological adjustment of adolescents with hearing impairment are as follows: home environment (β=0.624), school environment (β=0.570), age of onset (β=0.004), and degree of hearing loss (β=0.000) respectively. Home environment, school environment and personality types are important factors that enhanced psychological adjustment of adolescents with hearing impairment. Therefore, the government, parents and other stakeholders who are involved in the education of adolescents with hearing impairment should create an atmosphere that could enhance their psychological adjustment.